Desarrollo osteológico de la columna vertebral y del complejo caudal de larvas de Lutjanus guttatus (Perciformes: Lutjanidae) en condiciones de cultivo - Rodríguez-Ibarra, Luz Estela (2015)
The spotted rose snapper (Lutjanus guttatus) is an important commercial species in Mexico with good culture potential. The osteological study at early stages in this species is an important tool to confirm normal bone structure and for the detection of malformations that may occur during early development. This study was carried out in order to evaluate and describe the normal osteological development of the vertebral column and caudal complex of this species grown under controlled conditions. For this, a total of 540 larvae of L. guttatus, between 2.1 and 17.5mm of total length (TL), were cultured during 36 days; culture conditions were 28ºC, 5.74mg/L oxygen and 32.2ups salinity with standard feeding rates. To detect growth changes, a sample of 15 organisms was daily taken from day one until day 36 of post-hatch (DPH). Samples were processed following standard techniques of clearing, and cartilage (alcian blue) and bone staining (alizarin red). Results showed that the vertebral column is composed of nine vertebrae in the abdominal region, and 14 vertebrae including the urostyle in the caudal region. The development of the axial skeleton starts with the neural arches and haemal arches at 3.8mm TL. Caudal elements such as the hypurals and parahypural began to develop at 4.1mm TL. Pre-flexion and flexion of the notochord and the formation of all hypurals were observed between 5.3 and 5.8mm TL. Ossification of the vertebrae in the abdominal region and in some neural arches initiated at 9.5mm TL. In the caudal region, all the neural and haemal arches ossified at 10.2mm TL. All the abdominal vertebrae and their respective neural arches and parapophyses ossified at 11.2mm TL, while the elements of the caudal complex that ossified were the hypurals, parahypurals and modified haemal spines. All caudal fin rays, 12 neural spines and 3 haemal arches were ossified by 15.5mm. The complete ossification process of this specie under laboratory culture conditions was observed when larvae reached 17.3mm TL on 36 DPH. Detailed analysis of the osteological structures will allow a reference description to evaluate and detect malformations that may occur during the larval culture of the spotted rose snapper.